Functional Impact of Aerobic Exercise on Cardiovascular Autonomic Function, Peripheral Neuropathy Gait and Balance, Depression, and Quality of Life in Parkinson Disease. - Amgad Gabr , Mohamed Said , Shaimaa Maklad , Seham Abdelsadek , Sahar Fares Ahmed , Reham Ahmed , Aisha Abdellateef , Ahmed Khalifa, Marwa Salah- Eldien Abd-Elraouf, Amr Shehata, Mona Hussein, Taher Abd Elkareem, Abdelaal Alkhouly, Shimaa Fouad; Marwa Mohiy Eldin, Ahmed Abd-Elrhman, Suzan Elshishtawy, Noha O. Shawky, Wael A. Khattab , Albayoumi AB Fouda, Mohammad O. Zarad, Passant Hewady (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:Parkinson's disease (PD) is a progressive neurological disorder marked by the degeneration of neurons that produce dopamine in the substantia nigra area. This results in symptoms such as tremors, rigidity, bradykinesia, and difficulty maintaining balance. These symptoms significantly affect the individual's quality of life. Aim of the work: We aimed to assess the functional impact of aerobic exercise on cardiovascular autonomic function, peripheral neuropathy (gait and balance), depression, and quality of life in Parkinson’s disease. Patients and Methods: The current investigation is a two-arm parallelrandomised controlled trial. The sample was chosen using a non-probabilistic method. A random 1:1 ratio was used to assign the candidates to one of the 2 groups:25 case in the exercise interventions group and 25 case as control group (no invasive intervention). Result: As regard motor “Nerve conduction study” of popliteal and Tibialis nerve at both lower limbs, Na+/I− symporter (NIS L) score, “Brain-derived neurotrophic factor” (BDNF) , quality of life score , “Beck Depression Inventory” (BDI) score there was insignificant differences between two groups at baseline however, after six weeks, a marked improvement was noted in interventional group vs control. Conclusion: It was found that aerobic activity could lead to enhancements in motor NCV in popliteal fossa, and Tibial nerve, sural sensory nerve NCV, TINETTI gait and balance test, clinical neuropathy score, NIS L score, BDNF, quality of life score, BDI score.